‘Yo antes no reciclaba y esto me cambio por completo la consiencia’: intercultural citizenship education in the English classroom - Porto, Melina (2018)
This article describes a telecollaboration project about the environment in the primary English as a foreign language classroom carried out in 2013/2014 between Argentina and Denmark. It combines English language teaching with intercultural citizenship education and forms part of a network of projects in Europe, the US and East Asia. This is the only one set in the primary school context and in Latin America. After some preparatory work, the Argentinian and Danish children met online through Skype, using English, Spanish and Danish, to design a collaborative poster to raise awareness of the importance of taking care of the environment. Conversational and documentary data were collected and analysed qualitatively, in this case focusing on the Argentinian perspective. With a critical literacy conceptualisation, the project demonstrates growth in self/intercultural awareness, criticality and social justice responsibility, and the emergence of a sense of community of transnational peers amongst the children involved.